Subproteomic profiling of sarcolemma from dystrophic mdx-4cv skeletal muscle - Sandra Murphy; Margit Zweyer; Michael Henry; Paula Meleady; Rustam R. Mundegar; Dieter Swandulla; Kay Ohlendieck (Data in Brief, 2018)
The proteomic data presented in this article provide supporting information to the related research article ''Proteomic analysis of the sarcolemma-enriched fraction from dystrophic mdx-4cv skeletal muscle'' (Murphy et al., 2018) [1]. In the associated research article, the sarcolemma from normal versus dystrophic skeletal muscle was analyzed by mass spectrometry-based proteomics. Sarcolemma vesicles were enriched by a lectin agglutination method and then analyzed by liquid chromatography tandem mass spectrometry. Here we provide additional datasets on proteins with decreased versus increased abundance in dystrophin-deficient muscle plasma membranes.